Avoidant authority: The effect of organizational power on decision-making in high-uncertainty situations - Shortland, Neil D.; McCusker, Maureen E.; Alison, Laurence; Blacksmith, Nikki; Crayne, Matthew P.; Thompson, Lisa; Gonzales, Joseph; McGarry, Presley; Stevens, Catherine (Frontiers in Psychology, 2023)
Individuals in positions of power are often required to make high-stakes decisions. The approach-inhibition theory of social power holds that elevated power activates approach-related tendencies, leading to decisiveness and action orientation. However, naturalistic decision-making research has often reported that increased power often has the opposite effect and causes more avoidant decision-making. To investigate the potential activation of avoidance-related tendencies in response to elevated power, this study employed an immersive scenario-based battery of least-worst decisions (the Least-Worst Uncertain Choice Inventory for Emergency Responses; LUCIFER) with members of the United States Armed Forces. In line with previous naturalistic decision-making research on the effect of power, this research found that in conditions of higher power, individuals found decisions more difficult and were more likely to make an avoidant choice. Furthermore, this effect was more pronounced in domain-specific decisions for which the individual had experience. These findings expand our understanding of when, and in what contexts, power leads to approach vs. avoidant tendencies, as well as demonstrate the benefits of bridging methodological divides that exist between “in the lab” and “in the field” when studying high-uncertainty decision-making.